A novel multi-criteria spatial analysis approach for evaluating development prospects of geothermal resources: A case-study from Guangdong Province, China - Yongyi Li; Ghaffar Ali; Lianhua Ma (Results in Engineering)
Geothermal resources are renewable and environmentally friendly energy sources with distinctive advantages such as local sourcing, good stability, and minimal land occupation. Therefore, the accurate assessment of geothermal resources development prospects holds significant importance for its utilization. This study uses factors such as geothermal resource potential, topography, transportation accessibility, energy demand, economic scale and population size to develop a multi-criteria decision tool for evaluating the geothermal resource development prospects. Subsequently, analytic hierarchy process and entropy weighting method are employed to integrate subjective and objective weights. An improved comprehensive weight method is utilized to calculate the Technique for Order of Preference by Similarity to Ideal Solution score, providing an assessment of the development prospects across 315 geothermal resources sites in Guangdong province. Furthermore, spatial distribution patterns and spatial correlations of geothermal resources development prospects are analyzed using GeoDa software through Exploratory spatial data analysis (ESDA). The research findings reveal a significant positive spatial correlation in the development prospects of geothermal resources, characterized by both high-high and low-low cluster and dispersion phenomena. The Greater Bay Area (GBA) exhibits the highest level of geothermal resources development prospects, with scores ranging between 0.3 and 0.446, whereas most other areas demonstrate lower scores, predominantly below 0.1 (A score of 1 indicates the highest development prospects and 0 indicates the lowest development prospects). These findings serve as valuable references for policymakers, geothermal industry developers, and stakeholders involved in geothermal resources utilization, considering the demand for clean energy, the geothermal resources in the GBA are more worthy to be developed.